Association between place of birth and timely breastfeeding initiation among Cambodian women: a population-based study - Raleigh M. Harriott; Zelalem T. Haile; Ilana R. Azulay Chertok; Mohammad Rifat Haider (BMC, 2022)
Abstract Background Enhancing timely breastfeeding initiation within the first hour postpartum is a goal the WHO's Early Essential Newborn Care (EENC) and Baby-friendly Hospital Initiative (BFHI) aim to achieve globally. However, many health professionals and facilities have yet to adopt these guidelines in Cambodia, impeding timely initiation progress and maternal-infant health goals. Methods This secondary data analysis used the 2014 Cambodia Demographic and Health Survey (CDHS) data of 2,729 women who gave birth in the two years preceding the survey to examine the association between place of birth and timely breastfeeding initiation. Descriptive statistics, chi-square test and multivariable logistic regression were performed. Pairwise interaction terms between place of birth and each covariate were included in the regression model to examine the presence of multiplicative effect modification. Results The prevalence of timely breastfeeding initiation was 62.9 percent. Most women gave birth in public health facilities (72.8%) followed by private health facilities (15.9%) and at home (11.2%). The proportions of timely breastfeeding initiation differ by place of birth (p < 0.001). In the multivariable model, there was a significant interaction between place of birth and household wealth index and between place of birth and residence on timely initiation. Among women who reside in poor households, the odds of timely initiation were lower among women who gave birth at home compared to those who gave birth in public health facilities, adjusted odds ratio (95% confidence interval) 0.43 (0.21, 0.88). For urban settings, the odds of timely breastfeeding initiation were lower among women who gave birth in private health facilities compared to those who gave birth in public health facilities 0.52 (0.36, 0.75). For rural settings, the odds of timely breastfeeding initiation were lower among women who gave birth at home compared to those who gave birth in public health facilities 0.55 (0.31, 0.97). Conclusions Wealth index and residence moderated the association between place of birth and timely breastfeeding initiation in Cambodia. To improve breastfeeding outcomes and eliminate practices impeding timely initiation, breastfeeding advocacy programs need greater integration and follow-up in Cambodia's health systems, including among home birth attendants and private health facilities.